The Impact of Optic Nerve Movement on Intracranial Radiation Treatment - Qing, Kun; Nie, Ke; Liu, Bo; Feng, Xue; Stone, James R.; Cui, Taoran; Zhang, Yin; Zhu, Jiahua; Chen, Quan; Wang, Xiao; Zhao, Li; Parikh, Shreel; et al. (Frontiers in Oncology, 2022)
Purpose In radiotherapy, high radiation exposure to optic nerve (ON) can cause optic neuropathy or vision loss. In this study, we evaluated the pattern and extent of the ON movement using MRI, and investigated the potential dosimetric effect of this movement on radiotherapy. Methods MRI was performed in multiple planes in 5 human subjects without optic pathway abnormalities to determine optic nerve motion in different scenarios. The subjects were requested to gaze toward five directions during MRI acquisitions, including neutral (straight forward), left/right (horizontal movement), and up/down (vertical movement). Subsequently, the measured displacement was applied to patients with peri-optic tumors to evaluate the potential dosimetric effect of this motion. Results The motion of ON followed a nearly conical shape. By average, the anterior end of ONs moved with 10.8 ± 2.2 mm horizontally and 9.3 ± 0.8 mm vertically, while posterior end has negligible displacement. For patients who underwent stereotactic radiotherapy to a peri-optic tumors, the movement of ON in this measured range introduced non-negligible dosimetric effect. Conclusion The range of motion of the anterior portions of the optic nerves is on the order of centimeters, which may need to be considered with extra attention during radiation therapy in treating peri-optic lesions.